Carácter, razón y pasión en la ética de Aristóteles - Vallejo Álvarez, Ximena (2023)
In this article we pretend to expose briefly the place of desire, reason and character within the framework of teleological explanation about human reason purposed by Aristotle in his Ethic for Nicomacus. Our philosophical research central question can be formulated in two ways: how to understand the rationality in desire or what means rationalized desire? In order to offer a possible answer to these questions, it is necessary to do a circumlocution that give us some comprehension elements about the relationship between passion and reason; then, we will try to explain some Aristotle’s practical philosophy topics and, finally, we will expose an explanation and interpretation sketch of their basis